Influence of stabilisers on the catalytic activity of supported Au colloidal nanoparticles for the liquid phase oxidation of glucose to glucaric acid: understanding the catalyst performance from NMR relaxation and computational studies. Issue 7 (22nd March 2023) - Monti, Eleonora; Ventimiglia, Alessia; Forster, Luke; Rodríguez-Aguado, Elena; Cecilia, Juan Antonio; Ospitali, Francesca; Tabanelli, Tommaso; Albonetti, Stefania; Cavani, Fabrizio; Rivalta, Ivan; D'Agostino, Carmine; Dimitratos, Nikolaos
Abstract : Impact of stabilisers on the catalytic performance of supported Au colloidal nanoparticles for the liquid phase oxidation of glucose to glucaric acid. Abstract : Supported Au colloidal nanoparticles have been prepared in the presence of stabilising polymers, such as, PVA, PVP and PEG (polyvinylalcohol, polyvinylpyrrolidone, polyethylene glycol). The effect of the polymer to Au weight ratio was investigated, for the synthesis of Au nanoparticles with varying particle size and particle size distribution. By varying the polymer/Au wt/wt ratio, Au nanoparticles with mean diameters from 3 to 8 nm were synthesised. The synthesised Au catalysts were studied in the liquid phase oxidation of glucose to glucaric acid under alkaline conditions. We demonstrated that the choice of polymer and polymer to Au weight ratio, have an important influence in terms of catalytic activity and yield to glucaric acid. The highest yield to glucaric acid (22%) was obtained using Au–PVA catalysts. A strong deactivation was observed using Au catalysts. Further evaluation of the possible reasons for deactivation were investigated using experimental, computational and NMR relaxation studies.